Managing technology in higher education : strategies for transforming teaching and learning - Bates, Tony, 1939-; Sangra, Albert, 1960- (San Francisco, CA.: Jossey-Bass, 2011)
'Universities continue to struggle in their efforts to fully integrate information and communications technology within their activities. Based on examination of current practices in technology integration at 25 universities worldwide, this book argues for a radical approach to the management of technology in higher education. It offers recommendations for improving governance, strategic planning, integration of administrative and teaching services, management of digital resources, and training of technology managers and administrators. The book is written for anyone wanting to ensure technology is integrated as effectively and efficiently as possible.'--
Includes bibliographical references and index.
Keywords: Education, Higher -- Effect of technological innovations on; Information technology -- Management